(untitled) (JURNAL ULET (Utility, Earning and Tax), 2023)
This study aims to determine the financial performance of Regina Collection’s in 2019-2020 which is viewed based on activity and profitability as well as performance appraisal. Using descriptive research methods. The object of research is the financial performance of Regina Collection’s. The type of data used in this study is a primary data source. The data collection technique in this study is the interview technique method. The results of this study show that Regina Collection’s in terms of activities have not been able to manage its assets. This can be seen from the turnover of assets in 2019 as much as 0.58 times and in 2020 as much as 0.66 times. Then the activity is declared unhealthy. Meanwhile, based on profitability, it is viewed from the net profit margin in 2019 of 0.10 percent and in 2020 as much as 0.02 percent. In addition, Regina Collection’s performance based on profitability in terms of Net Profit Margin performance has decreased because in 2020 there was a problem with the Covid19 pandemic so that profit before tax decreased.